1999
DOI: 10.1161/01.cir.100.11.1253
|View full text |Cite
|
Sign up to set email alerts
|

Monounsaturated Fatty Acids and Risk of Cardiovascular Disease

Abstract: for the Nutrition Committee T his report summarizes our current understanding of how monounsaturated fatty acids (MUFAs) affect risk for cardiovascular disease (CVD). This is a topic that has attracted considerable scientific interest, 1-3 in large part because of uncertainty regarding whether MUFA or carbohydrate should be substituted for saturated fatty acids (SFAs) and the desirable quantity of MUFA to include in the diet. MUFAs in the US DietMUFAs are distinguished from the other fatty acid classes on the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
168
0
11

Year Published

2002
2002
2022
2022

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 319 publications
(182 citation statements)
references
References 76 publications
3
168
0
11
Order By: Relevance
“…With regard to dietary fat, there is growing consensus concerning the beneficial effects of MUFA and/or PUFA in terms of preventing diabetes and CVD (21)(22)(23)(24) , but the detrimental effect of SFA is still controversial (25,26) . In our study, the highest total fat intake was found in the vegetal/fat group, followed by the animal products group.…”
Section: Discussionmentioning
confidence: 99%
“…With regard to dietary fat, there is growing consensus concerning the beneficial effects of MUFA and/or PUFA in terms of preventing diabetes and CVD (21)(22)(23)(24) , but the detrimental effect of SFA is still controversial (25,26) . In our study, the highest total fat intake was found in the vegetal/fat group, followed by the animal products group.…”
Section: Discussionmentioning
confidence: 99%
“…It can therefore be safely assumed that a significantly higher score could have been expected for this component in Spanish children, had the original HEI method of dietary assessment been used. Secondly, whereas the index assesses total fat and saturated fatty acid intakes under two separate heads, it takes no account of unsaturated fatty acid intake (Hu et al, 1999;Kris-Etherton, 1999). The Mediterranean dietFrich in fats with a predominance of monounsaturated fatty acidsFhas been associated with a marked and significant reduction in total mortality (Trichopoulou & Vasilopoulou, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…The EDPG guidelines specify LDL values of 3.0 or less, more than 3.0 but equal to or less than 4.0, and more than 4.0 mmol/l as low risk, at risk and high risk, respectively and recommend lipidlowering therapy in patients with LDL values of 3.0 mmol/l or more [13]. American Heart Association guidelines for cardiovascular risk factors in diabetic patients, state that LDL values should be maintained under 2.6 mmol/l or 2.0 mmol/l if multiple risk factors are present [17]. In the CODE-2 study, LDL measurements were carried out in only 27% of patients.…”
Section: National Comparisons Of Hba Ic'mentioning
confidence: 99%